Perlindungan Hukum Terhadap Korban Eksploitasi Seksual pada Tindak Pidana Perdagangan Orang di Yogyakarta - Annas, Gilang Kresnanda; Asyrofisyauqi, Ahmad Izzul (Universitas Proklamasi 45, 2024)
Legal protection for victims should be considered in the running of justice in Indonesia. Protection of victims talks about fulfilling a victim's rights, both in and after the judicial process. One form of legal protection that is quite interesting to discuss is related to legal protection for victims of sexual exploitation. This research seeks to answer the forms of protection for victims of sexual exploitation of criminal acts of human trafficking in the Special Region of Yogyakarta and the obstacles in implementing legal protection for victims of sexual exploitation of criminal acts of human trafficking in the Special Region of Yogyakarta. This type of research is field research using an empirical juridical approach. The results of this research show that legal protection for victims of sexual exploitation (sex trafficking) of criminal acts of human trafficking in the Special Region of Yogyakarta has not been fulfilled, because there are still victims who are neglected due to several factors, including, legal officials who lack competence in handling victims of sexual exploitation. Victims who are not cooperative in the protection process or law enforcement process, inadequate protection facilities, including shelters as rehabilitation places whose needs have not been met, as well as a team of psychologists and legal counselors who are not proportional to the number of victims. The obstacles to implementing forms of legal protection for victims are that the mechanism for blocking the assets of perpetrators or convicts has not been regulated, causing the right to restitution not to be fulfilled optimally. Low public knowledge and awareness of exploitation and its impacts, causes victims not to feel like they are victims of sexual exploitation.